Molecular and biochemical responses of horticultural plants and crops to heat stress - Shafiei Masouleh, Seyedeh Somayyeh; Sassine, Youssef Najib (Ornamental Horticulture, 2020)
Various abiotic stresses affect growth and development of plants and one of them that causes severely decreasing the horticultural and crop yields is the heat stress worldwide. In this paper, the effects of heat (more than 30-35 °C in different species) stress on the horticultural plants and crops, and its effects on inducing other stresses, including osmotic and oxidative stresses are discussed. Plants show the molecular and biochemical responses after receiving environmental signals such as high temperatures and tolerate undesirable conditions.